2015
DOI: 10.1186/s12940-015-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Street-level noise in an urban setting: assessment and contribution to personal exposure

Abstract: BackgroundThe urban soundscape, which represents the totality of noise in the urban setting, is formed from a wide range of sources. One of the most ubiquitous and least studied of these is street-level (i.e., sidewalk) noise. Mainly associated with vehicular traffic, street level noise is hard to ignore and hard to escape. It is also potentially dangerous, as excessive noise from any source is an important risk factor for adverse health effects. This study was conducted to better characterize the urban sounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 31 publications
1
31
1
5
Order By: Relevance
“…New York City noise has been the focus of a plethora of studies investigating: noise levels in relation to air pollutants and traffic [10,11], noise exposure from urban transit systems [12,13,14] and noise exposure at street level [15]. All of these highlight the fact that noise is an underrepresented field in urban health and found that average levels of outdoor noise at many locations around the city exceed federal and international guidelines set to protect public health.…”
Section: New York City Noisementioning
confidence: 99%
“…New York City noise has been the focus of a plethora of studies investigating: noise levels in relation to air pollutants and traffic [10,11], noise exposure from urban transit systems [12,13,14] and noise exposure at street level [15]. All of these highlight the fact that noise is an underrepresented field in urban health and found that average levels of outdoor noise at many locations around the city exceed federal and international guidelines set to protect public health.…”
Section: New York City Noisementioning
confidence: 99%
“…[2] In particular, road traffic is a major source of environmental noise in North American and European cities. [14][15][16][17] Noise due to road traffic is expected to increase with the continuing worldwide shift toward urbanization.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the links between urban noise pollution and issues of population health appear to be more recent, the metrics for noise pollution are well established. The L EQ represents the average noise level received over a period of time that typically spans minutes to hours, whereas the L MAX represents the very highest exposure received over a period of seconds or even milliseconds (50,61). A-weighted decibels (dBA) are an expression of the relative loudness of sounds in air as perceived by the human ear.…”
Section: Pollutionmentioning
confidence: 99%